Exponential Temperature-Dependent Parameters for Thermodynamic and Structural Properties of Al-Ti Melt - Gohivar, R. K.; Yadav, S. K.; Koirala, R. P.; Adhikari, D. (BIBECHANA, 2022)
Thermodynamic and structural properties of Al-Ti melt have been estimated in the framework of Redlich-Kister (R-K) polynomial using linear temperature-dependent (T-dependent) interaction parameters above melting temperatures. These calculations show the existence of the artificial inverted miscibility gaps (artifacts) at temperatures 2000 K, 2500 K, and 2700 K. Therefore, interaction parameters are assumed to vary exponentially with temperature and have been optimised for excess free energy of mixing. The artifacts do not appear in the calculation of these properties of the concerned alloy when these optimized parameters are used.BIBECHANA 19 (2022) 75-82